Scale-invariant binary phase-only matched filter using a ferroelectric-liquid-crystal spatial light modulator. - Wilkinson, T; O'Brien, D; Mears, R (1994)
We describe the implementation of a scale-invariant binary phase-only matched filter using a 128 × 128 ferroelectric spatial light modulator. A 5-dB discrimination was obtained between a 10-image training set of highly correlated characters (E's and F's) over a scale range of 1.0 to 1.5.